Epigenetic Regulation of Mammary Epithelial Differentiation and Lineage Plasticity. - Skibinski, Adam. (2017)
Abstract: Lineage-committed cells of many tissues exhibit substantial plasticity in contexts such as wound healing and tumorigenesis, but the regulation of this process is not well understood. Here, I studied the molecular mechanisms that either allow mammary epithelial cells (MECs) to transdifferentiate or dedifferentiate in specific contexts. I identified the Hippo transducer WWTR1/TAZ in a screen of transcription factors able to prompt lineage switching of mammary epithelial cells from a luminal cell fate to a basal cell fate. Forced expression of TAZ in luminal cells induces them to adopt basal characteristics, and depletion of TAZ in basal/myoepithelial cells leads to luminal differentiation. Accordingly, loss of TAZ during mammary gland development leads to an imbalance of luminal and basal populations as well as branching defects. Moreover, TAZ interacts with components of the SWI/SNF complex to modulate lineage-specific gene expression. In addition, copy-number amplification of TAZ is associated with the basal-like molecular subtype of breast cancer and independently predicts prognosis in patients with basal-like disease. Collectively, these findings uncover a new role for Hippo signaling in the determination of lineage identity through recruitment of chromatin remodeling complexes.; Thesis (Ph.D.)--Tufts University, 2016.; Submitted to the Dept. of Cell, Molecular & Developmental Biology.; Advisor: Charlotte Kuperwasser.; Committee: Grace Gill, Phil Hinds, Jonathan Garlick, and Jim Schwob.; Keywords: Developmental biology, and Oncology.